(untitled) (Nordic Journal of African Studies, 2011)
This article compares three hiatus resolution strategies, viz., glide formation, secondary articulation and vowel elision in Karanga and Nambya, two southern Bantu languages spoken in Zimbabwe. The overall analysis is couched in Optimality Theory (hereafter OT). The strategies operate across a prefix and a stem as well as across a nominal stem and a diminutive suffix. In both languages, glide formation is the default strategy and when blocked by phonotactic constraints, secondary articulation kicks in. In turn, when secondary articulation is blocked by OCP-driven constraints, V1 elision occurs. The main inter-language difference occurs when V1 is a coronal vowel and is preceded by a consonant; Karanga deletes V1 regardless of the quality of the preceding consonant because it does not allow palatalized consonants. In contrast, Nambya which allows some palatalized consonants employs secondary articulation with all other consonants except when the preceding consonant is palatal–where V1 is elided. In sum, in Karanga and Nambya, the quality of V1 and whether it is preceded by a consonant or not as well as the type of consonant preceding it determine which strategy between glide formation, secondary articulation and elision repairs the dispreferred configuration-hiatus.